THE EFFICIENCY OF BIOLOGICAL THERAPY AND THE FEATURES OF HUMORAL IMMUNITY IN PATIENTS WITH SYSTEMIC LUPUS ERYTHEMATOSUS - A. A. Mesnyankina; S. K. Solovyev; E. A. Aseeva; E. L. Nasonov (Научно-практическая ревматология, 2018)
Objective: to investigate the effect of various biological agents (BAs), including combined treatment with rituximab (RTM) and belimumab (BLM), on the activity of systemic lupus erythematosus (SLE) and to evaluate their efficacy and impact on some parameters of humoral immunity.Subjects and methods. BAs were prescribed to 54 patients with a reliable diagnosis of SLE with high and medium activity according to SLEDAI-2K; 40 of them received RTM, 7 – BLM; 7 – combined therapy with RTM and BLM. Clinical and laboratory examinations were made in all the patients at the time of their inclusion and then every 3 months during a year. The results were assessed using SLEDAI-2K, BILAG index, Lupus Erythematosus National Assessment (SELENA)-SLEDAI Flare index (SFI) (a moderate, severe exacerbation), and SLE Responder Index (SRI).Results and discussion. At 3, 6, and 12 months after start of therapy, the use of BAs in all the patients resulted in a disease activity reduction. It was statistically significant (p < 0.00001) in the RTM group; and no statistical analysis was carried out in the BLM and RTM+BLM groups due to the small numbers of patients. At the same time, there was a progressive decrease in the levels of anti-double-stranded DNA (ds-DNA) antibodies (Abs) and an increase in the concentration of the complement fractions C3 and C4 in the RTM and RTM+BLM groups (p < 0.05) at one-year follow-up. After 12 months of therapy with BAs, there was a decrease in IgG (p < 0.02) and IgM (p < 0.03) levels; but overall it remained within the reference ranges. Prior to therapy, irreversible organ damages were recorded in 23 (42.6%) of the 54 patients. The increased damage index at 12 month was observed only in patients receiving RTM, which is probably due to the use of higher-dose glucocorticoids.Conclusion. All three methods of therapy with BAs in SLE patients demonstrated good efficiency shown as a significant decrease in clinical and laboratory activity measures that were assessed by SLEDAI-2K and the levels of anti-ds-DNA and complement components C3 and C4. The decrease in immunoglobulin levels did not go beyond the reference values. Therapy with BLM and RTM+BLM allowed for managing patients with the low and average doses of oral glucocorticoids, which contributed to the reduction of not only the activity, but also risk of irreversible organ damages.